విమర్శక వతంసులు (వ్యాస సంపుట) - Rama Rao, Acharya S.V. (Andhra Saraswata Parishath, 2011)
This book is about essays on Telugu Critics
Vimarsaka Vathamsulu (Vyasa Samputa)
Keywords: Telugu; విమర్శక వతంసులు (వ్యాస సంపుట); Vimarsaka Vathamsulu (Vyasa Samputa); Literature; Telugu; Telugu